Cu(OAc)2/FOXAP complex catalyzed construction of 2, 5-dihydropyrrole derivatives via asymmetric 1, 3-dipolar cycloaddition of azomethine ylides to ethynyl ketones1. Issue 7 (22nd July 2015) - Tang, Fei-Fei; Yang, Wu-Lin; Yu, Xingxin; Deng, Wei-Ping
<x xml:space="preserve">Abstract</x> Cu(OAc)2/FOXAP catalyzed asymmetric 1, 3-dipolar cycloaddition of azomethine ylides to ethynyl ketones, affording 2, 5-dihydropyrroles in good to excellent yields and excellent enantioselectivities.